The Sociological Study of Stress: An Analysis and Critique of the Stress Process Model - Au, Anson (European Journal of Mental Health, 2017)
The stress process model in the sociological study of stress has changed over the thirty years of its use, developed continually to reflect changes in society and to include intellectual refinement. This paper represents a review that aims to do the same, filling the gaps in the original model with the inclusion of major developments in its structure and new social dimensions. An examination of the model’s key components reveals: its causes and manifestations, the intervention of resources that moderate its effects, and its consequences on an individual in terms of mental health and social adversities. In visitation of the dynamics of the stress process, I present a critical analysis that involves an investigation of the findings of research literature while considering recent trends, including the decline of the nuclear family and the influence of non-Western cultures among immigrants and minority groups. Thus, asserted on the case that the considerations undertaken by literature are again at a point requiring intellectual reform, this critique endeavours to articulate an updated, foundational version of the original model and to offer appraisals that could lend themselves as points for further development and study.